A New Approach to Policy : The Case for Strengthening Organizational Conditions to Improve Early Childhood Care and Education Quality / Maia Connors, Angela Farwig and Beth Kenefick. - Connors, Maia; Farwig, Angela; Kenefick, Beth; Wagner, Maureen; Pacchiano, Debra (Distributed by ERIC Clearinghouse, 2018)
This brief report outlines policy approaches that have the potential to strengthen the organizational conditions of early care and education (ECE) programs as a means to quality improvement. The ultimate goal is to enhance the ability of all ECE programs to support young children's learning and development by improving the quality of teaching and learning in classrooms. Evidence shows that children learn more in high-quality classrooms, yet recent research has illuminated the limitations of current policy approaches to strengthening classroom practice. A new approach is proposed in this brief report: Advocating for and implementing policies aimed at improving the organizational conditions of ECE programs as a means to stimulate quality improvement at the classroom level.
Availability: Ounce of Prevention Fund. 33 West Monroe Street Suite 2400, Chicago, IL 60603. Tel: 312-922-3863; e-mail: info@theounce.org; Web site: http://www.theounce.org.
Abstractor: ERIC.
Educational level discussed: Early Childhood Education.
Keywords: Educational Improvement.; Educational Quality.; Educational Policy.; Early Childhood Education.; Child Care.; Child Development.; Learning Processes.; Teaching Methods.; Classroom Techniques.; Faculty Development.; Teacher Qualifications.; Teacher Education Programs.; Teacher Role.; Administrator Role.; Teacher Salaries.; Standards.; Decision Making.; Communities of Practice.; Organizational Change.; Cooperation.